The Role of Language Training in the Process of Foreign Students’ Socialization in the Educational and Cultural Environment of Higher Educational Institutions. - Билык, Е. Н. (Teaching Languages at Higher Educational Establishments at the Present Stage. Intersubject Relations, 2016)
The article deals with socializing potential of foreign students’ language training in the educational and cultural environment of higher educational institutions. The author emphasizes the necessity of taking into account a socio-cultural component, the teacher’s role as an agent of socialization in the process of education